Mobilising Canada: The National Resources Mobilization Act, the Department of National Defence, and Compulsory Military Service in Canada, 1940-1945 - Byers, Daniel (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1996)
AbstractCompulsory military service took on the most organized, long-term form it has ever had in Canada during the Second World War. But few historians look beyond the politics of conscription to study the creation, administration or impact of a training system that affected more than 150,000 people. Faced with the Mackenzie King government's policy of conscripting manpower only for home defence, and their own need for overseas volunteers, Army leaders used conscripts raised under the National Resources Mobilization Act to meet both purposes. This paper explores the Army's role in creating and administering the compulsory military training system during the war, the pressures put on conscripts to volunteer for overseas service, and the increased resistance to volunteering that resulted by 1944. The consequences of the Army's management of conscription came very much to shape the political events that took place in 1944, and cannot be fully understood outside that context.